2013
DOI: 10.1177/0307174x1304000706
|View full text |Cite
|
Sign up to set email alerts
|

The Optical and Sorption Properties of Films of Polyvinyl Alcohol with Silver Nanoparticles

Abstract: It has been established that, with increase in the silver concentration in polymer film, there is a shift in position of the maximum in absorption spectra into the longwave region. Bands in the absorption spectra in the range 400-510 nm correspond to surface plasmon resonance (SPR) of the silver nanoparticles. It is shown that silvercontaining film is an adsorbent in relation to water vapour over saturated solutions of ammonium chloride, potassium nitrate, and sodium sulphate, with maximum sorption observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the plant-mediated synthesis of NPs, observation of bands in the range of 400-530 cm -1 was mainly ascribed to stretching vibrations of the polyaromatic system and indicated the success of the reaction and formation of NPs (18,25,50,51). Moreover, presence of multiple bands, especially between 400-450 cm -1 in the FTIR spectra of both NPs, suggests that particle size was significantly varying because of anisotropy existing in the reaction outcome (52). Overall, FTIR results demonstrated that proteins, aromatic amines, reducing sugars and polyphenols were acted as both reducing and capping agents in phytofabrication and stabilization of NPs.…”
Section: Ecolimentioning
confidence: 99%
“…In the plant-mediated synthesis of NPs, observation of bands in the range of 400-530 cm -1 was mainly ascribed to stretching vibrations of the polyaromatic system and indicated the success of the reaction and formation of NPs (18,25,50,51). Moreover, presence of multiple bands, especially between 400-450 cm -1 in the FTIR spectra of both NPs, suggests that particle size was significantly varying because of anisotropy existing in the reaction outcome (52). Overall, FTIR results demonstrated that proteins, aromatic amines, reducing sugars and polyphenols were acted as both reducing and capping agents in phytofabrication and stabilization of NPs.…”
Section: Ecolimentioning
confidence: 99%
“…In the plant-mediated synthesis of AgNPs, observation of bands in the above range was mainly ascribed to stretching vibrations of various glucose rings and identified residual biomolecular traces. The obtained FTIR spectra of AgNPs clearly expose band growth in the above range of wavenumber that further intensifies in the gamut of absorption regime between 500-400 cm −1 , indicating the success of the reaction and formation of AgNPs [12,29,34]. The appearance of two maxima near 430 and 415 cm −1 in the absorption spectra also indicates particles with reduced size.…”
Section: Uv-visible and Ftir Spectroscopy Profile Of Agnpsmentioning
confidence: 82%
“…In such studies, maximum absorption observed near 430 cm −1 wavenumber indicates a high conversion of AgNPs from their precursor. Nevertheless, the presence of multiple bands, especially between 400 and 450 cm −1 in the spectra, suggests that particle size was significantly varying because of anisotropy existing in the reaction outcome [34]. In WNPs, double bands at 3,630 and 3,650 cm −1 were ascribed to O-H stretching of alcohols.…”
Section: Uv-visible and Ftir Spectroscopy Profile Of Agnpsmentioning
confidence: 99%